Characterization of Postgraduate Programs Offers in International Relations in Costa Rica and Internationally - Raúl Fonseca-Hernández; Carlos Humberto Cascante-Segura; Yendry Arce-Marín; Lizeth Abarca-Jiménez (Universidad Nacional, Costa Rica, 2016)
The objective of this document is to analyze the factors characterizing the postgraduate programs related to the discipline of International Relations in Costa Rica, and also other international references. This paper intends to be a useful tool to observe the characteristics and approaches of teaching this discipline in Costa Rica. In other knowledge fields, the variables described in this study can be used to perform similar analysis; likewise, students of this discipline can analyze the characteristics and approaches of the postgraduate programs offer in this area to create their own criteria. This research was conducted from December 2014 to February 2015, and it included nineteen national and nine international postgraduate programs. The information was collected from secondary sources of data retrieved from websites of each postgraduate program. The data were also collected from primary sources with telephone calls and e-mails. As a conclusion from the study, there is a relevant debate between the needs of academic rigor and the flexibility the market requests in terms of education conditions associated with the postgraduate programs.